2021
DOI: 10.1016/j.asmr.2021.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using Bone–Patellar Tendon–Bone Allograft in Patients Aged 50 and Older Leads to Improved Activity Levels and Acceptable Patient-Reported Outcomes

Abstract: Purpose To evaluate patient-reported outcomes in patients aged 50 years and older undergoing anterior cruciate ligament reconstruction (ACLR) using bone–patellar tendon–bone (BPTB) allograft with minimum 2-year follow-up. Methods A retrospective review was performed on a consecutive series of patients aged 50 and older who underwent ACLR using BPTB allograft by a single surgeon with minimum 2-year follow-up. Postoperative International Knee Documentation Committee (IKDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…et al did present a similar result in their retrospective study after ACL reconstruction in a group of 69 patients but with a mean age of 33.4 years [27]. Sylvia et al recently reported that in patients over 50, the Tegner Activity Level was 5.3 after a 2 year follow-up [35]. Hence, we were able to conirm these results.…”
Section: Discussionsupporting
confidence: 83%
“…et al did present a similar result in their retrospective study after ACL reconstruction in a group of 69 patients but with a mean age of 33.4 years [27]. Sylvia et al recently reported that in patients over 50, the Tegner Activity Level was 5.3 after a 2 year follow-up [35]. Hence, we were able to conirm these results.…”
Section: Discussionsupporting
confidence: 83%
“…Studies are conducted using different graft types like hamstring tendon autograft, quadriceps tendon autograft, or bone–patellar tendon–bone autograft at patients older than 50 years of age have shown improved functional knee scores and high rates of return to sportive activitie. 40 , 41 , 42 Corona et al. 43 showed comparable results with younger patients at a large systematic review.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have evaluated the benefit of ACLR in middle-aged patients and found outcomes comparable to those in younger patients [6,11,25,26,29,37]. Furthermore, some well-documented researches have demonstrated excellent clinical results following ACLR in selected and motivated patients older than 50 years [7,9,17,22,23,27,35,36]. In addition, few studies have reported that ACLR in active patients over 60 years without OA could restore knee stability and allow patients to return to preinjury activity levels [1,18,31,33].…”
Section: Introductionmentioning
confidence: 99%